Viability and germination of Hechtia perotensis (Bromeliaceae) seed - Elizalde, Violeta (2017)
Endemic populations of Hechtia perotensis have been described in Puebla and Veracruz, Mexico. Good quality seed collections can be used in conservation, research and ecological restoration. To evaluate seed quality of wild and endemic species, some compounds are used as effective promoters of germination, such as potassium nitrate (KNO3) and gibberellic acid (AG3), because they increase seed germination capacity and reduce latency. The triphenyl tetrazolium chloride (tetrazolium) test correlates seed viability because it is based on the activity of dehydrogenases in live tissues that catalyze mitochondrial respiration. The objective of this study was to obtain information on size and weight of capsules and seeds and seed germination and viability of H. perotensis, collected in Veracruz in the year 2012 and 2015. The hypotheses were 1) that seed germination and viability are independent of the year of collection, 2) that there is a tetrazolium concentration that can identify seed viability better than others, and 3) that pretreatment with KNO3 or AG3 improves seed germination. Seed germination was assessed using a completely randomized design with three treatments (control and the germination promoters 0.2 % KNO3 and 500 mg/L AG3), four treatments for the viability test (control, 0.2, 0.5 and 1.0 % of tetrazolium) and six replicates for each treatment. A total of one hundred seeds for germination experiments, and 25 seeds for the viability test were used. The results between and within years were analyzed with ANOVA and multiple comparison with the Tukey test. The proportion of non-germinated seeds was quantified along with the number of normal and abnormal seedlings, seeds with viable embryo, seeds without embryo, and seeds with low or no viability. On average, for the 2012 collected sample, 36 % had viable embryos, 7 % had low viability, 24 % were not viable and 33 % had no embryo. This result was significantly different from the 2015 sample, for which 87 % of seed showed viable embryos, 10 % had low viability, 0 % was not viable and 3 % had no embryo. Seed germination was also significantly different between years (22 and 92 %) Pregerminative treatments did not improve germination. Seed germination and viability of H. perotensis significantly varied between years of seed collection.